Adsorption behaviour of microplastics on the heavy metal Cr(VI) before and after ageing. (September 2022) - Li, Yinghua; Zhang, Yue; Su, Fei; Wang, Yiyan; Peng, Linlin; Liu, Deze
Abstract: As the important carriers of environmental pollutants, microplastics have a significant impact on the migration, transformation and toxicology of heavy metals. In this paper, the adsorption behavior of Cr(VI) on PE/PS/PA microplastics under UV irradiation was studied. The research results show that the adsorption capacity of original PA is the strongest, followed by PS and PE. The specific surface area of the aged microplastics increased and new functional groups were formed, so the adsorption of three microplastics for Cr(VI) was stronger than that before aging. The average saturation adsorption of Cr(VI) by PA/PS/PE increased respectively from 730.69 μg/g, 146.11 μg/g and 75.61 μg/g to 736.31 μg/g, 318.75 μg/g and 136.78 μg/g. The Langmuir and Freundlich models showed that the adsorption is more consistent with the Freundlich model, indicating that adsorption is mainly based on multi-molecular layer adsorption on non-homogeneous surfaces. In the Cu–Cr polluted water, Cu has different effects on the adsorption behavior. Cu can promote the adsorption of Cr(VI) by PE and PS, while inhibited the adsorption by PA. In addition, environmental conditions such as temperature, pH and dissolved organic matter also have significant effects on adsorption behavior. Mechanistic analysis confirmed that electrostatic interaction plays an important role. Secondly, based on the surface physicochemical properties of the microplastics, surface complexation and van der Waals forces also significantly enhance the adsorption of Cr(VI) on the aged microplastics. Graphical abstract: Image 1 Highlights: Absorption effect of Cr(VI) by original MPs: PA > PS > PE. Cu inhibits the adsorption of Cr(VI) by PA, but promotes the adsorption on PE and PS. Electrostatic interactions dominate the adsorption behavior. Surface complexation and van der Waals forces can also affect adsorption.